2008
DOI: 10.1590/s0102-311x2008000500029
|View full text |Cite
|
Sign up to set email alerts
|

Associação entre circunferência abdominal e hipertensão arterial em mulheres: Estudo Pró-Saúde

Abstract: This study aimed to estimate the prevalence of hypertension according to levels of abdominal circumference (AC) IntroduçãoÍndices antropométricos distintos, em particular o índice de massa corporal (IMC) para classificação de sobrepeso e obesidade, têm sido utilizados para avaliar a associação entre excesso de peso e morbidade cardiovascular. Ainda que seja uma excelente medida de obesidade, o IMC não considera a variação na distribuição da gordura corporal 1 .Vários estudos têm registrado que a circunferên… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
16

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 14 publications
(18 reference statements)
0
3
0
16
Order By: Relevance
“…Some authors mention that the abdominal circumference is more associated to hypertension than to obesity. 30 A similar study points to an increased association of abdominal circumference with hypertension. 11 Recently, studies have demonstrated the severe characteristic of an increased abdominal circumference, as it represents a risk for the development of chronic non-transmissible diseases, among which cardiovascular diseases stand out.…”
mentioning
confidence: 75%
“…Some authors mention that the abdominal circumference is more associated to hypertension than to obesity. 30 A similar study points to an increased association of abdominal circumference with hypertension. 11 Recently, studies have demonstrated the severe characteristic of an increased abdominal circumference, as it represents a risk for the development of chronic non-transmissible diseases, among which cardiovascular diseases stand out.…”
mentioning
confidence: 75%
“…Foi possível observar que, para o ImC, a amostra se apresentou na faixa de sobrepeso de acordo com os pontos de corte da WHO (2000), enquanto o perímetro da cintura indicou risco aumentando para obesidade associada a complicações metabólicas, seguindo os critérios propostos por Hasselmann et al (2008). Outro ponto a ser levado em consideração é a pontuação média obtida no QCN, indicando nível moderado de conhecimento nutricional.…”
Section: Resultsunclassified
“…Quanto à hipertensão, alguns autores trazem dados alarmantes acerca de sua prevalência e de seus índices de incidência em crianças e adolescentes, pois enfatizam, através de pesquisas como a de Sorof et al (2004) MONTEIRO, 2007;HASSELMANN et al, 2008;GUIMARÃES et al, 2008).…”
Section: Resultsunclassified